0065 Using fully immersive simulation to train defence anaesthetists for contingency operations. (2nd November 2015) - Jones, Clinton; Hunt, David; Clitheroe, Edwin; Round, Jonathan; Mercer, Simon
Abstract : Background/context: In the future, it is likely that Defence Anaesthetists will be required to work in small teams on contingency operations using some equipment that is not available in the NHS. The Triservice Anaesthetic Apparatus (TSAA) 1 is a 'draw-over' anaesthetic machine and does not have a CE Mark. We designed a two-day fully immersive simulation course mapped to the CPD matrix of the Royal College of Anaesthetists to allow practice prior to development and completion of the Higher Military Module. Methodology: The course was conducted in a traditional high fidelity simulation centre. Following an introduction, mannequin familiarisation and a practical demonstration of the TSAA, participants undertook fully immersive scenarios as part of a small surgical team based around an acute hostage situation. Scenarios were based in a trauma team setting and the operating theatre with complex trauma patients. A video assisted debrief focused on non-technical skills, the use of the TSAA and Defence Guidelines. 2 Results/outcomes: 20/29 participants completed a reflective evaluation. 11/20 were consultants and 11/20 had never used TSAA. 12/20 strongly agreed (8/12 agreed) that the scenarios allowed an adequate opportunity to practice and troubleshoot. If deployed 13/20 agreed (5/20 strongly agreed) they would be confident conducting a General Anaesthetic with the TSAA. 5/20 strongly disagreed (10/20 disagreed) that they would have been happy to give a General Anaesthetic after just the introductory demonstration and lecture without the opportunity to undertake scenarios. Conclusions and recommendations: It is essential that Defence Anaesthetists are familiar with the equipment they will use on deployment. Familiarisation with equipment is vital to ensure patient safety. 3 This course was well received and has allowed the opportunity to practice in a fully immersive environment and has improved confidence with the TSAA. References: Houghton IT. The triservice anaesthetic apparatus. Anaesthesia 1981;36: 1094–1108 Ministry of Defence. Joint Doctrine Publication 4-03.1. Clinical Guidelines for Operations. September 2008; MOD, UK Gaba DM. Anaesthesiology as a model for patient safety in health care. BMJ 2000;320:785–788